Digital Journaling as A Mirror of Learning: Emotional and Cognitive Reflections from Language Learners - Dewi, Kadek Maya Cyntia; Suryati, Ni Wayan Novi; Rusanti, Putu; Wismadewi, I Gusti Agung Galuh; Susandi, Ni Kadek Ary (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Reflective activities is important to measure students’ engagement and understanding of the learning process (Zatalini & Assassi, 2025). In the digital age, journaling has become a valuable tool that allows students to express their thoughts, emotions and evaluation of classroom experiences (Bingöl, 2025). Digital journaling offers learners an accessible platform to articulate emotions, perceptions, and evaluations of their learning journey (Phetsut & Waemusa, 2022). Despite its potential, the use of digital journaling to capture students’ post-class reflections remains unexplored (Yaacob et al., 2020). digital formats will allow to give an immediate expression, integration of multimedia and greater flexibility, which can increase students' motivation and authenticity in reflection (Yunus et al., 2023). This study aimed to investigate students’ perspectives on the teaching and learning process through digital journaling and to identify emotional and reflective themes from their entries. Using qualitative descriptive design with 20 students enrolled in the Pusat Bahasa course submitted weekly digital journal reflection over 4 weeks. Thematic analysis revealed four key themes namely emotional responses, instructional perceptions, self-reflection on learning and suggestions for improvement (Riyanti, 2021). The findings showed that students frequently experienced positive emotions, enjoyed interactive and visual activities and become more aware of their learning progress. Many feedback also included ideas to enhance engagement such as incorporating games and small group activities. Digital journaling is a powerful reflective tool that fosters student’s introspection, metacognitive growth and contributes to more adaptive, learner-centered teaching practices.